Conselhos municipais de educação do Alto Tietê: constituição e funcionamento - Silva, Andrea Araujo De Arruda [UNIFESP] (2019)
This dissertation aimed to map the constitution of the Municipal Education Councils (CME) of the Alto Tietê region. A balance of the normative and organizational production of the Collegiate of this region was produced; From the documentary base accessible for 2017-2018, the Suzano City Council was selected and presented the volume of data that best evidenced the performance of its functions, thus allowing a more in-depth study on the participation of civil society in the formulation. of educational policies in this municipality. The constitution of the MEC in most Brazilian municipalities is due to the decentralization policies produced by the State reform, especially since 1990. As a theoretical reference was used the writings of Dropa (2004) and Adrião (2006); to contextualize the course of the Municipal Education Councils, Bordignon (2009), Lagares (2008) and Cury (2000). Fundamental documents for the understanding of educational policy also make up the sources of this research, such as: LDBEN 9394/96, CF 1988, CNE Opinion No. 30/2000 - CEB, among others. The work was developed in four (4) chapters; The first is the State Reform framework as an induction policy for decentralization and creation of Municipal Education Systems; The second chapter covers the democratic management through the bias of the Municipal Education Councils and the particularities of the constitution of the CME of each municipality of the Alto Tietê Region; The third chapter presents, based on the mapping analysis, the municipality with the largest volume of data available for further research; and finally, the fourth chapter shows an initial outline of the handling of the Suzano Municipality CME documents between 2017 and 2018. These data were analyzed in order to answer the following question: What can be verified regarding the participation of society? in the formulation of educational policies for the municipality of Suzano? Therefore, it is understood that the participation of civil society is essential to establish greater assertiveness regarding local educational policies, thus, analyzing how participation is effective in the WEC is essential for the improvement of educational quality and is therefore, the main focus of this dissertation.